FAEDAH SANKSI (KAFFARAH) BAGI MASYARAKAT PERSPEKTIF MAHMUD SYALTUT - Husnawadi, Husnawadi (STIS Darussalam Bermi, 2024)
This article aims to describe the kaffarah sanctions for society from Mahmud Syaltuts perspective, the method used in this research is descriptive qualitative research method, data collection is carried out by reading relevant research books such as texbooks, encyclopedias, scientific journals, dictionaries and others, then all data is analyzed critically then interpreted and presented in the form of a description. The research results show that the important benefits of implementing kaffarah sanctions are urgent to be revealed comprehensively so that they can be used as a reference in implementing kaffarah sanctions, according to Mahmud Shawtut, Allah has established kaffarah not only as an atonement for sins and a solution to overcome mistakes that occur to a Muslim, but more than that, so that a servant maintains his spiritual spirit and his relationship with his God.